The new bone formation in human maxillary sinuses using two bone substitutes with different resorption types associated or not with autogenous bone graft: A comparative histomorphometric, immunohistochemical and randomized clinical study - Pereira, Rodrigo dos Santos; Bonardi, João Paulo [UNESP]; Ouverney, Felippe Ricardo Frossard; Campos, Annelise Backer; Griza, Geraldo Luiz; Okamoto, Roberta [UNESP]; Hochuli-Vieira, Eduardo [UNESP] (FapUNIFESP (SciELO), 2021)
Objective: The aim of this study is to evaluate the new bone and connective tissue formation and the biomaterial remaining after maxillary sinus bone augmentation using 5 different bone substitutes. The osteocalcin immunolabeling was performed to demonstrate their calcification and the possibility of receiving dental implants. Methodology: 40 patients underwent maxillary sinus bone augmentation and were divided in 5 groups: Group 1 with 8 maxillary sinuses were grafted with autogenous bone graft (AB); Group 2 with 8 maxillary sinuses grafted with bioactive glass (BG); Group 3 with 8 maxillary sinuses grafted with bioactive glass added to autogenous bone graft (BG + AB) 1:1; Group 4 with 8 maxillary sinuses grafted with Bio-Oss (BO) and Group 5 with 8 maxillary sinuses grafted with Bio-Oss added to autogenous bone graft (BO + AB) 1:1. Results: In group AB, 37.8% of bone was formed in the pristine bone region, 38.1% in the intermediate and 44.5% in the apical region. In group BG, 43.6% was formed in the pristine bone, 37% in the intermediate and 49.3% in the apical region. In group BG + AB 1:1, 39.0% was formed in the pristine bone region, 34.8% in the intermediate and 36.8% in apical region. In group BO, 33.4% was formed in the pristine bone, 32.5% in the intermediate and 34.3% in the apical region. In group BO + AB 1:1, 32.8% was formed in the pristine bone, 36.1% in intermediate and 27.8% in the apical regions. The immunolabeling for osteocalcin showed an intensive staining for all groups, which could demonstrate the calcification of the bone formed. Conclusion: This study showed that the groups evaluated formed a suitable lamellar bone in the maxillary sinus reconstruction after six months of bone healing, thus being indicated to receive dental implants.
Keywords: Bioactive glass; Biomaterials; Bone regeneration; Bone substitutes; Sinus floor augmentation; Tissue physiology; Xenograft